Effect of Cryptorchidism on the Histomorphometry, Proliferation, Apoptosis, and Autophagy in Boar Testes - Xiaorui Fan; Yihui Liu; Meishan Yue; Weidong Yue; Gaoya Ren; Jingwen Zhang; Xinrong Zhang; Junping He (Animals, 2021)
Spontaneous unilateral cryptorchid boars have one testis in the abdomen or inguinal canal, causing its temperature to be at or near the body temperature, which impairs spermatogenesis, although the histomorphometry and molecular mechanisms underlying this process remain unclear. The aim of the present study was to determine the histomorphometry, proliferation, apoptosis, and autophagy alterations in spermatogonia and Sertoli cells in unilateral cryptorchid, scrotal (contrascrotal), and preweaning piglet (preweaning) testes. Histomorphometrical analysis of cryptorchid testes showed that the seminiferous tubules contained only Sertoli cells and a few spermatogonia, but did not contain post-meiotic germ cells. The number of spermatogonia markedly decreased, and the number of Sertoli cells did not change remarkably in cryptorchid testes. TUNEL assay results showed that apoptosis signals were predominantly observed in spermatogonia. In cryptorchid and contrascrotal testes, proliferating cell nuclear antigen (PCNA) and LC3 were located in spermatogonia. The number of PCNA-positive, TUNEL-positive, and LC3-positive germ cells was low, and the protein and mRNA levels of PCNA and LC3 were significantly decreased in cryptorchid testes. Taken together, the number of Sertoli cells did not change remarkably, whereas the number of germ cells decreased in the cryptorchid testes, compared with that in the contrascrotal testes. Insufficient proliferation, excessive apoptosis, and autophagy were involved in the regulation of the decrease in spermatogonia in cryptorchid boar testes.